Expert Information Prediction Modeling In Pcap Files - et. al., S. Leelalakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The cyber security field has more challenges and analysing pcap files for identifying the network traces provides important details. The web traffic consists of different types of transfer. Some data can be malicious and it can fall into different categories. Analysing and extracting features and applyying machine learning algorithms can prove to be more useful for indentifying the network information. Todays’ big data environment provides more way to security threats.